Foram os escravos decisivos na abolição da escravidão? Considerações a propósito de um livro de Nelly Schmidt - Marques, João Pedro (Africana Studia, 2020)
According to a much publicized thesis, the African rebel and runaway slaves were the first anti-slavery group of colonial history. Their resistance had undermined life in the colonies leading to the abolition of slavery and to the death of the colonial system. That is, the first and main agents of the abolition of slavery were those slaves and not the European and American abolitionists whose action would only be known, and mostly in a timid way, at the end of the XVIII century. Having as a starting point the critical review of a recent book by Nelly Schmidt – that reaffirms this thesis – this article intends to demonstrate that such a perspective is based, on one hand, on the mystification or misunderstanding of the objectives of the slaves’ escapes and rebellions, and, on the other hand, in a sub valorization of abolitionism.